Audit Tata Kelola Sistem Informasi di Instansi XYZ Menggunakan Framework COBIT 5 - Antara, I Putu Wahyu Bayu Putra (Universitas Multi Data Palembang, 2025)
Information system governance audits aim to determine the maturity level of information system governance based on existing problems in a company. The Bali Province Ministry of Religion Regional Office is one of the government agencies that serves the community by utilizing information systems. The Regional Office of the Ministry of Religion of Bali Province faces several problems in implementing the information system, such as errors in data input into the system by the admin and a slow system due to the large number of users using it. Therefore, it is important to carry out an information system audit using the COBIT 5 framework to find out and identify existing problems for smooth operations. This research aims to determine and provide recommendations for improvements regarding the level of maturity in the information system at the Regional Office of the Ministry of Religion, Bali Province.